Primary and secondary structure of hamster vimentin predicted from the nucleotide sequence. - Quax-Jeuken, Y E (1983)
The nucleotide sequence of two recombinant plasmids containing hamster vimentin cDNA was determined. The sequence comprises 1,640 base pairs and reveals virtually the total primary structure of vimentin and a large part of the 3' noncoding region. Secondary structure prediction methods allow the characterization of two distinct regions of the polypeptide chain, 135 and 145 residues long, which are able to form alpha helices organized in "coiled coils." Three nonhelical domains can be distinguished: a very basic NH2-terminal domain of at least 67 residues, a nonhelical region of 45 amino acids separating the two helix domains, and a COOH-terminal region of 55 residues, which contains an excess of acidic amino acids. The meaning of each of these domains of the vimentin polypeptide for the subunit and filament formation is discussed.